Konflik Sosial dalam Novel Padusi Karya Ka’bati: Tinjauan Struktural - Yusriman, Fadlillah, Amini Arbain (Universitas Andalas, 2023)
This research was carried out on the novel Padusi by Ka'bati which was published in Kakilangit Kencana in 2015. The problem that will be discussed in this novel is the form of social conflict that occurs in the novel Padusi by Ka'bati. This research also aims to explain the form of social conflict in Padusi's novel. This research is very useful for Indonesian literary treasures, this research will also enrich the world of Indonesian literary criticism and develop literature as a scientific discipline, therefore this research can also be used as literature in understanding social conflicts that occur in society. This research uses a structural approach. Meanwhile, the method used is a qualitative method which produces written works from texts that refer to social conflict. The data collection technique was carried out by carefully reading the novel, and the data analysis technique was carried out in a qualitative descriptive manner. After researchers conducted research on Padusi's novel, it can be concluded that the social conflict in this novel is conflict between individuals and individuals, conflict between individuals and groups, conflict between groups and groups. As well as describing the intrinsic elements in this novel in the form of characters and characterization, setting and theme.